2014
DOI: 10.1155/2014/852890
|View full text |Cite
|
Sign up to set email alerts
|

ModelingIn VitroCellular Responses to Silver Nanoparticles

Abstract: Engineered nanoparticles (NPs) have been widely demonstrated to induce toxic effects to various cell types. In vitro cell exposure systems have high potential for reliable, high throughput screening of nanoparticle toxicity, allowing focusing on particular pathways while excluding unwanted effects due to other cells or tissue dosimetry. The work presented here involves a detailed biologically based computational model of cellular interactions with NPs; it utilizes measurements performed in human cell culture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“… MN (size) Endpoint Biological level Species Reference nano-Al (80 nm) Functional viability Alveolar macrophages cell dynamics Rat [41] polyamidoamine dendrimer (PAMAM) Uptake/cytotoxicity (sub-)Cellular responses (e.g. ROS, apoptosis) for human keratinocyte and murine macrophages Human Murine [42] nano-Ag carbon black (10–20 nm) Pulmonary function Alveolar tissue Mouse [43] nano-Ag citrate-coated and PVP-coated In vitro inflammatory response Immune cell – macrophages and human monocyte-derived macrophages for cytokine study Human [44] …”
Section: Results On Available Pb Models Applicable To Mnsmentioning
confidence: 99%
See 2 more Smart Citations
“… MN (size) Endpoint Biological level Species Reference nano-Al (80 nm) Functional viability Alveolar macrophages cell dynamics Rat [41] polyamidoamine dendrimer (PAMAM) Uptake/cytotoxicity (sub-)Cellular responses (e.g. ROS, apoptosis) for human keratinocyte and murine macrophages Human Murine [42] nano-Ag carbon black (10–20 nm) Pulmonary function Alveolar tissue Mouse [43] nano-Ag citrate-coated and PVP-coated In vitro inflammatory response Immune cell – macrophages and human monocyte-derived macrophages for cytokine study Human [44] …”
Section: Results On Available Pb Models Applicable To Mnsmentioning
confidence: 99%
“…Finally, Mukherjee et al [44] developed a mathematical model that predicts the in vitro inflammatory response (i.e. expression levels of cytokines) of immune cells exposed to citrate-coated and PVP-coated nano-Ag in a culture system.…”
Section: Results On Available Pb Models Applicable To Mnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is a difficult to scale up nanoparticle production leading to limitation in market production. More importantly, the human immune system may be defenseless against particles on the nanoscale [80][81][82]. As a result, tiny solid particles can cause irritation in the lungs and potentially cause lung damage and cancer.…”
Section: Challenges Of Nanoparticlesmentioning
confidence: 99%
“…Consequently, any analysis of the residence time distribution, clearance and biological response of NPs in any tissue system requires a detailed characterization of their form, size and surface reactivity, as these change dynamically with time. The effects of transformation processes were investigated for an in vitro culture of alveolar macrophages [ 14 ], demonstrating that NP dosimetry to cells is significantly different when relevant transformation processes are considered. Hinderliter et al [ 6 ] also showed that the actual amount and form of the NPs reaching the cells over time are markedly different when NP diffusion and settling area are taken into account.…”
Section: Introductionmentioning
confidence: 99%